CARS FOR INTERIOR DESIGN WEBSITE DESIGN SEAT "USARITA" USING MACROMEDIA DREAMWEAVER 8.0 - Ahmad Yuleindra Pratama; Linda Wahyu Widianti, SKom, MMSI (Jurnal Sistem Informasi, 2008)
In the development of information technology, the rapid current, so the more easy for every person in getting information. Information can be obtained in various ways, especially for modification of car seat covers. Therefore, efforts Repair Car seat holster "USARITA" offers products such as materials and car seats are offered online as well as for ordering products.